Insects: Friend or Foe? Color and Learn! - Jennifer L. Gillett-Kaufman (EDIS)
Not just a coloring book, but an interactive learning experience! This educational handout is perfect for classroom use, homeschool, or just a rainy (or snowy, if you are not in Florida) day. This activity will help connect kids and adults with the amazing diversity of animals for which we have articles in the UF/IFAS Featured Creatures database. This coloring book can be printed front to back on a standard 8.5 by 11 inch sheet of paper. Once you have your paper and coloring tools in hand, learn more about these creatures and decide what colors to use by reading more about them and visiting the web links for each insect. This 4-page fact sheet was written by Jennifer L. Gillett-Kaufman, and published by the UF Department of Entomology and Nematology, February 2014.